Surface cyclotron x-modes propagating along a boundary of uniform plasma - Girka, V.A.; Puzyrkov, S.Yu. (Физическая инженерия поверхности, 2007)
Propagation of surface cyclotron X - modes (SCXM) at the second harmonics of electron and ion cyclotron frequencies along interface of uniform semi-bounded plasma is under the consideration. It is proved both analytically and numerically that SCXM are the eigenmodes of a planar magnetoactive plasma waveguide structure consisted of a metal wall with dielectric coating and uniform plasma filling. An external steady magnetic field is supposed to be oriented parallel to the plasma interface, so it is perpendicular to the group velocity of the considered extraordinary polarized waves. The influence of the plasma density on the SCXM dispersion has been studied. The theoretical investigation is carried out using the kinetic equation for plasma particles under the conditions of a weak plasma spatial dispersion and taking into the account ordinary case.